Physics of Lakes Volume 1: Foundation of the Mathematical and Physical Background - Hutter, Kolumban; Wang, Yongqi; Chubarenko, Irina P.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Info text
Mathematical Prerequisites -- A Brief Review of the Basic Thermomechanical Laws of Classical Physics -- Fundamental Equations of Lake Hydrodynamics -- Conservation of Angular Momentum - Vorticity -- Turbulence Modelling -- Introduction to Linear Waves -- The Role of the Distribution of Mass within Water Bodies on Earth -- Vertical Structure of Wind-induced Currents in Homogenous and Stratified Waters -- Phenomenological Coefficients of Water.
Keywords: Geography; Physical geography; Oceanography; Ecology; Earth Sciences; Earth Sciences, general; Geoecology/Natural Processes; Classical Continuum Physics; Geophysics/Geodesy.; Oceanography